Urine Screening and 9 Years’ Medical Record System Follow-Up Among School Students in Wenzhou, China - Chen, Tingting; Yang, Qing; Xu, Hong; Gong, Yinv; Guo, Xiaoling; Lin, Hongzhou; Yang, Jianhuan; Zhuang, Jieqiu; Lan, Junwei; Chu, Maoping; Wang, Dexuan (Frontiers in Pediatrics, 2022)
School urinary screening programming can be useful for early detection of renal and urinary disorders. However, urine screening is not included in the school health check-up in our region. Therefore, from February to December 2012, 12497 primary and secondary school students were screened for urinalysis by the dipstick method. Children having abnormal results in the initial screening would receive a repeat urinalysis 2 weeks later, and were admitted to the Second Affiliated Hospital and Yuying Children’s Hospital of Wenzhou Medical University (WMU) and followed up via an electronic medical record system while the children with the positive results of both screening tests. Additionally, 9 years’ electronic data related to initial and new onset urinalysis abnormalities of our hospital of 12497 students were reviewed, in order to assess the timing of screening and methods.Among these screened students, 719 (5.76%) positive individuals received a repeat urinalysis 2 weeks later. During the 9-year medical record system follow-up period, 5 children had renal biopsies, and two had a diagnosis of IgA nephropathy, while the remaining 3 children were diagnosed as thin basement membrane disease (TBM), Primary nephrotic syndrome (PNS) and suspected of C3 glomerulopathy, respectively. If urine screening can be added to school health check-up in our region, more children with an abnormal urinalysis result but had no clinical manifestations can be found, which will contribute to enabling early detection of urine abnormalities and allowing for early treatment.